2019
DOI: 10.29333/ejgm/104620
|View full text |Cite
|
Sign up to set email alerts
|

Fasting may be an alternative treatment method recommended by physicians

Abstract: Objective: Fasting is a practice found in many cultures both ancient and modern. Although, fasting (religious or otherwise) causes many physiological, biochemical, metabolic and spiritual changes in the body, there is no clear scientific consensus on its beneficial effects on health. Also, despite the popularity and potential promise of therapeutic fasting as a preventive measure, little is known about the prevalence of therapeutic fasting use. This study was performed to discuss whether could fasting be part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…During refeeding following the daily "fast," glucose levels rise and ketones are cleared with increased protein synthesis allowing growth and repair allowing more efficient cellular performance, leading to cellular resilience and disease resistance as a longterm adaptation [38]. A time-restricted eating regimen where evening food intake is restricted reportedly improves postprandial insulin and glucose handling due to alignment of circadian rhythm with diurnal food intake [41]. Several variations of time-restricted eating and terms are described in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…During refeeding following the daily "fast," glucose levels rise and ketones are cleared with increased protein synthesis allowing growth and repair allowing more efficient cellular performance, leading to cellular resilience and disease resistance as a longterm adaptation [38]. A time-restricted eating regimen where evening food intake is restricted reportedly improves postprandial insulin and glucose handling due to alignment of circadian rhythm with diurnal food intake [41]. Several variations of time-restricted eating and terms are described in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IF has been studied for years (98,99). It has been indicated that the implementation of several fasting programmes into practice has the potential to improve the disease prognosis and can reverse the disease condition, particularly in patients with T2D and prediabetes (20,100,101). While this has been reported among adults with T2D (102), this approach has not been investigated widely among children and young adults.…”
Section: Effects Of the Covid-19 Pandemic On Patients With Type 2 Diabetes Among Children And Young Adultsmentioning
confidence: 99%
“…Alternate day fasting has been identified by fasting every other day and during the fasting day, the followed protocol is either to limit the food intake to only 25% of the daily food intake (500 calories/day) or to consume zero calories, while returning to the normal healthy diet during the eating day (101). On the other hand, TRF is characterised by the limitation of the daily consumed food over a specific period during the day with no calorie restriction and this time limit varies from 4 to 12 h (109).…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…Actually, intermittent fasting exerts well-being effect on different body organs and leads to a better metabolic health status in humans (21). Apart from its well-documented beneficial effects on the brain, heart, liver, intestine, and muscles, recent studies show that it ameliorates the immune system by rejuvenation and regeneration of stem cells, reducing inflammation and oxidative stress, reducing autoimmunity, improving cell repair (autophagy), and promoting healthy aging (21). These benefits encourage many physicians to recommend it as an alternative treatment for patients with asthma, hypertension, diabetes, rheumatoid arthritis, multiple sclerosis, systemic lupus erythematosus, and even cancer (21,22).…”
Section: Fasting Immunomodulatory Effect In Experimental Studiesmentioning
confidence: 99%